2020
DOI: 10.15604/ejef.2020.08.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Economic Growth in African Largest Economy

Abstract: The study examines the nexus between tourism and economic growth in Nigeria from 1995-2017. Data were sourced from World Development Indicator and World Tourism Council data base online. Autoregressive distributed lag model (ARDL) was used in analyzing the data. The result of the Bounds test shows that the value of the Fstatistics is greater than the value of the upper bound of the Pesaran, Chin and Smith statistics table at 1% level of significance, which showed that there is a long run relationship among eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
1
0
4
Order By: Relevance
“…This study found no Granger causality for the full sample 1960-2011; instead, a twoway causality relationship was documented for the 1985-1990 sample period. The non-causal relationship between tourism and economic growth is also found by Salawu (2020) for the case of Nigeria, and the bidirectional causal relationship between the variables is also documented for the case of South Africa by Phiri (2016). For the Pacific Islands, Narayan (2010) investigates the relationship between tourism and economic growth for the four Pacific island nations.…”
Section: Literature Reviewmentioning
confidence: 82%
“…This study found no Granger causality for the full sample 1960-2011; instead, a twoway causality relationship was documented for the 1985-1990 sample period. The non-causal relationship between tourism and economic growth is also found by Salawu (2020) for the case of Nigeria, and the bidirectional causal relationship between the variables is also documented for the case of South Africa by Phiri (2016). For the Pacific Islands, Narayan (2010) investigates the relationship between tourism and economic growth for the four Pacific island nations.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Bu nedenle turizmin ekonomik büyüme üzerindeki etkisi en çok araştırılan konuların başında gelmektedir. Literatür incelendiğinde turizm faaliyetlerinin ekonomik büyümeyi desteklediğini gösteren (Ghali, 1976;Balaguer ve Jorda, 2002;Bahar ve Bozkurt, 2010;Jin, 2011;Algan ve Gencer, 2015;Simundic ve Kulis, 2016;Sarıdoğan, 2019;Salawu, 2020) birçok çalışmaya rastlamak mümkündür. Ayrıca, Akdeniz havzası ülkelerinden olan Türkiye'nin turizm gelirleri ve ekonomik büyümesi arasındaki ilişki (Özcan, 2015; Şahin, 2018) ve Afrika ülkelerinin turizm gelirleri ile ekonomik büyümesi arasındaki ilişkiyi inceleyen birçok çalışma literatürde yer almaktadır (Fayissa vd., 2007;Salawu, 2020;Kumar vd., 2021).…”
Section: Literatür Taramasıunclassified
“…Literatür incelendiğinde turizm faaliyetlerinin ekonomik büyümeyi desteklediğini gösteren (Ghali, 1976;Balaguer ve Jorda, 2002;Bahar ve Bozkurt, 2010;Jin, 2011;Algan ve Gencer, 2015;Simundic ve Kulis, 2016;Sarıdoğan, 2019;Salawu, 2020) birçok çalışmaya rastlamak mümkündür. Ayrıca, Akdeniz havzası ülkelerinden olan Türkiye'nin turizm gelirleri ve ekonomik büyümesi arasındaki ilişki (Özcan, 2015; Şahin, 2018) ve Afrika ülkelerinin turizm gelirleri ile ekonomik büyümesi arasındaki ilişkiyi inceleyen birçok çalışma literatürde yer almaktadır (Fayissa vd., 2007;Salawu, 2020;Kumar vd., 2021). Araştırmalar turizmin gelişmekte olan ülkelerde kilit rol oynadığı ortaya koymakla birlikte, gelişmiş ülkelerde de turizm gelirleri istihdamın devamlılığı açısından oldukça önemli bir role sahiptir.…”
Section: Literatür Taramasıunclassified
See 2 more Smart Citations